Elaboracion de manual para la preparacioón y presentación de información exógena para la Clínica Oftalmológica Quindío S.A. por el año gravable 2011 (2012)
Some companies have a formal obligation to prepare and report tax information exogenous to the National Tax and Customs Office (DIAN) who are determinate annually by external resolutions, which taxpayers have to do it. The Ophthalmologic Clinic Quindío SA. belongs to a category of informants groups, which is why the development of a manual for the preparation and presentation of exogenous clinical information for the taxable year 2011, was developed taking into account the applicable rules for this year that is resolution 11429 of 31 October 2011 and Article 631 of the Tax Code and the procedures in each of the stages of design.